Voice-specific proper name anomia ('phonoanomia') after bilateral temporal hemorrhagic brain lesions. (March 2022) - Moretta, Pasquale; Trojano, Luigi
Abstract: We describe a patient who developed bilateral temporal lesions due to a haemorrhagic stroke. One year after onset, he showed marked apperceptive prosopagnosia and could not name people from their voices, although he had spared semantic knowledge about people he could not name and could access this knowledge from people's voice. Importantly, the patient was able to retrieve proper name of persons after their description and was able to name sounds and songs; he could also retrieve proper names of monuments, towns and cartoon characters upon visual presentation. No further relevant cognitive impairment was present. This clinical picture represents the auditory counterpart of prosopanomia and could be defined 'phonoanomia'. This case report suggests that naming people from their voice implies specific retrieval processes, and pose specific constraints to theoretical models of person recognition.